Excitatory VTA to DH projections provide a valence signal to memory circuits - Yuan Han (Nature Portfolio, 2020)
The neuronal pathway that signals the positive or negative value of memories is not well understood. Here, the authors report that an excitatory projection from the ventral tegmental area to the dorsal hippocampus carries the valence information, contributing, especially in females, to the recurrence of fear and to drug seeking behavior.